2007
DOI: 10.1590/s0102-695x2007000100002
|View full text |Cite
|
Sign up to set email alerts
|

Plants traditionally used against malaria: phytochemical and pharmacological investigation of Momordica foetida

Abstract: RESUMO: "Plantas tradicionalmente utilizadas contra malária: investigação fi toquímica e farmacológica de Momordica foetida". Folhas de Momordica foetida tradicionalmente usadas para tratar sintomas de malária em partes da África Oriental foram estudadas in vitro com respeito à sua atividade antimalárica. Utilizando-se o teste de incorporação de hipoxantina [ 3 H] a atividade antiplasmódica dos extratos hidrofílico e lipofílico contra a cepa sensíveis a cloroquina poW e o clone multiresistente Dd2 de Plasmodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Other flavonoid molecules such as catechin, epicatechin, quercetin, apigenin, myricetin, luteolin, and kaempferol have been reported in other Momordica species (Kubola and Siriamornpun 2008;Horax et al 2010;Nagarani et al 2014). Interestingly, Froelich et al (2007) extracted some of the identified flavonoids in M. foetida using methanol as solvent, and this is an indication that PHWE technique is comparable to traditional solvent-based methods. Furthermore, the extracted molecules are known to exhibit a wide spectrum of health-promoting properties.…”
Section: Compound Identification: Their Nutritional and Pharmacologicmentioning
confidence: 83%
“…Other flavonoid molecules such as catechin, epicatechin, quercetin, apigenin, myricetin, luteolin, and kaempferol have been reported in other Momordica species (Kubola and Siriamornpun 2008;Horax et al 2010;Nagarani et al 2014). Interestingly, Froelich et al (2007) extracted some of the identified flavonoids in M. foetida using methanol as solvent, and this is an indication that PHWE technique is comparable to traditional solvent-based methods. Furthermore, the extracted molecules are known to exhibit a wide spectrum of health-promoting properties.…”
Section: Compound Identification: Their Nutritional and Pharmacologicmentioning
confidence: 83%
“…Stomach ache (Hamill et al, 2000). Antimalarial activity detected (Froelich et al, 2007;Waako et al, 2005). Roots for malaria, (Tabuti, 2008).…”
Section: Rukararwe Leaves Omwihuramentioning
confidence: 99%
“…Cucurbitaceae (African cucumber, bitter gourd, bitter melon) a medicinal plant used traditionally as an antidiabetic, an emetic, a laxative, a tonic, and to treat anaemia, arthritis, colds, fever, gout, infertility, kidney stones, peptic ulcers, stomach ache and intestinal helminthes 12 . It is also used as an antimalarial, together with related species, and as an abortifacient [13][14][15] . Some pharmacological and safety studies of this herb have been carried out 16,17 .…”
Section: Introductionmentioning
confidence: 99%